An evaluation of undergraduate student nurses' gameful experience while playing an escape room game as part of a community health nursing course. (August 2021) - Anguas-Gracia, Ana; Subirón-Valera, Ana B.; Antón-Solanas, Isabel; Rodríguez-Roca, Beatriz; Satústegui-Dordá, Pedro J.; Urcola-Pardo, Fernando
Abstract: Background: The integration of innovative strategies to teaching and learning in higher education, such as escape room games, can enhance the acquisition of key professional competencies including communication, teamwork and critical thinking. Objectives: This study aimed to evaluate undergraduate student nurses' gameful experience while playing an escape room game as part of a nursing course. Design: Cross-sectional descriptive study. Participants: A total of 126 third year student nurses enrolled in the "Community Health Nursing II" course. Method: The escape room game took place in a classroom at the Faculty of Health Ciences. The measures included the GAMEX scale in its Spanish version and a self-reported questionnaire to evaluate the student's outcome of scape room game immediately after the end of the activity. Results: The vast majority (99.21%) considered the escape room game to be an appropriate and an innovative teaching and learning strategy. The mean score for each of the GAMEX dimensions was over 3, with the exception of Absence of negative effects. Our results suggest that the students enjoyed playing the game (mean = 4.40; SD = 0.71), that escape room games should be integrated in nursing courses (mean = 4.54; SD = 0.74) and that playing the game increased their motivation for learning (mean = 3.06; SD = 1.09). Gender differences were observed in the GAMEX Dominance dimension ( p < 0.005). Conclusion: Gamification in general, and escape rooms in particular, have proven to be a valid tool for the acquisition of professional competencies in higher education. Highlights: The integration of gamification in higher education can enhance the acquisition of key professional competencies. Escape room games are an innovative and motivating educational strategy. Escape room games allow students to apply theoretical knowledge to a case study and solve problems.